2010
DOI: 10.1007/s13187-010-0080-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Nutritional Education Pamphlet for Low Literacy Pediatric Oncology Caregivers in Central America

Abstract: Background A culturally appropriate nutrition education pamphlet was developed and validated for low-literacy caregivers in Honduras, El Salvador, and Guatemala. Methods The pamphlet was developed after a preliminary survey of pediatric oncology nurses in the 3 countries to assess the need for education materials, caregiver literacy levels, and local eating habits. Experts in nutrition and low-literacy patient education and nurses validated the pamphlet’s content and design. Results and Conclusions Nurses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
8
0
3
Order By: Relevance
“…For example, Shah et al (2018) tested a pamphlet on health and mood addressing people older than 55 years, in order to increase their will to be screened for depression. Garcia et al (2010) developed an educational pamphlet to increase knowledge on oncological children’s nutrition addressed to low-literacy caregivers. Other researchers found that a pamphlet on proper antibiotic use was more efficacious for increasing knowledge of parents who consulted it compared to a control group who did not consult any material, although it was less efficacious than an animated video ( Schnellinger et al, 2010 ).…”
Section: Background and Rationalementioning
confidence: 99%
“…For example, Shah et al (2018) tested a pamphlet on health and mood addressing people older than 55 years, in order to increase their will to be screened for depression. Garcia et al (2010) developed an educational pamphlet to increase knowledge on oncological children’s nutrition addressed to low-literacy caregivers. Other researchers found that a pamphlet on proper antibiotic use was more efficacious for increasing knowledge of parents who consulted it compared to a control group who did not consult any material, although it was less efficacious than an animated video ( Schnellinger et al, 2010 ).…”
Section: Background and Rationalementioning
confidence: 99%
“…Interview guides were developed on the basis of a literature review of previously conducted assessments including parental education needs and parent experiences after learning their child’s diagnosis. 14-16 Interviews were audio recorded using a mobile application, and notes were taken during the interview. Interviews were translated and transcribed into a master document, and specific quotes and common messages were categorized into broad themes.…”
Section: Methodsmentioning
confidence: 99%
“…13 This is helpful for pediatric oncology programs, but research conducted in LMICs has highlighted certain additional factors to consider when developing educational programs, including the socioeconomic level of the parents, cultural or language barriers, and the availability of qualified personnel or resources to create informational materials. 14…”
Section: Introductionmentioning
confidence: 99%
“…Diet education for patients and families in LMICs is complicated by low literacy, limited availability of trained personnel, and a lack of materials ( 81 ). To provide successful education for low-literacy patients and caregivers, culturally appropriate instruments and pictorial-based material must be developed; this has been successfully done in several LMICs ( 82–84 ). To ensure that food provision and nutrition education are prioritized in LMIC cancer centers, research should be conducted to demonstrate if these low-cost and low-resource measures can effectively improve body composition and clinical outcomes.…”
Section: Current Status Of Knowledgementioning
confidence: 99%